Sleep disordered breathing and its impact on the course of chronic non-communicable lung diseases - I. D. Bespalova; U. M. Mitrichenko; Yu. I. Koshchavtseva; D. V. Kapitanova; A. Z. Badmaev; S. Agaeva; O. V. Zhukovskaja; V. M. Kolmakova; T. V. Belyakova; A. V. Teteneva; E. B. Bukreeva; V. V. Boyarko; et al. (Бюллетень сибирской медицины)
The lecture synthesizes and analyzes the findings of research concerning the impact of sleep disordered breathing (SDB) on the progression of the most prevalent chronic non-infectious lung diseases (CNLDs). SDB, including conditions, such as snoring, sleep hypoventilation syndrome, and obstructive and central sleep apnea syndrome, constitutes a significant medical concern due to its high prevalence and adverse health consequences. SDB is regarded as an independent risk factor for the development and progression of a range of CNLDs. Timely diagnosis and management of SDB may serve as an effective preventive measure against severe manifestations and complications associated with this group of diseases.